Ultrasonographic appearance of the ileocecocolic junction in cats with salmonellosis - Brzozowska, Magdalena; Rapp, Martin; Vermeire, Simon; Klich, Daniel; Stanczyk, Ewa (Frontiers in Veterinary Science, 2025)
Salmonellosis is a bacterial infection caused by Salmonella spp. When it affects the gastrointestinal tract of cats, it has a predilection for the ileocecocolic junction. Abdominal ultrasound is a valuable tool in diagnosing gastrointestinal diseases. This retrospective, single-center case series study aimed to describe the ultrasonographic abnormalities of the ileocecocolic junction in feline patients with confirmed Salmonella infection. One hundred cats presenting with gastrointestinal symptoms were tested for Salmonella between 2019 and 2022; 70 tested positive, and 30 tested negative. All of them underwent ultrasonographic examination. The positive group showed a significantly thickened wall of the ileum (p < 0.001, range: 1.9–5.7 mm, mean = 3.25 mm, SD = 0.66), caecum (p < 0.001, range: 2.1–3.9 mm, mean = 2.87 mm, SD = 0.49), and ascending colon (p < 0.05, range: 1–3.1 mm, mean = 1.47 mm, SD = 0.55) in comparison to the negative group. In the positive group, the ileocecal lymph nodes were significantly larger in diameter (p < 0.001, range: 2.7–7.8 mm, mean = 4.9 mm, SD = 1.15). All Salmonella-positive cats had focal hyperechoic mesenteric fat, and 23% (16/70) had focal peritoneal effusion at the ileocecocolic junction. The combination of the thickening of the intestinal wall at the ileocecocolic junction, focal hyperechoic mesenteric fat, peritoneal effusion and regional lymphadenopathy may indicate Salmonellosis in cats with compatible clinical signs. Including this diagnosis may prompt further testing, leading to early recognition and effective treatment, resulting in better patient outcomes. Diagnosing this disease is also important as Salmonellosis carries a zoonotic risk, with the potential transmission between pets and humans.